PENGEMBANGAN MEDIA PEMBELAJARAN FINGER PAINTING UNTUK MENINGKATKAN KEMAMPUAN MOTORIK ANAK TK - Ruminingsih; Purwulan, Heni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to develop finger painting learning media and examine its feasibility, practicality, and effectiveness in improving kindergarten children's fine motor skills. The study was conducted because learning activities for motor development were still limited, less varied, and not fully aligned with children's need for direct, playful, and sensory-based experiences. This research used a Research and Development design adapted from Borg and Gall, covering needs analysis, product planning, prototype development, expert validation, limited testing, field testing, revision, and dissemination. The subjects were group B kindergarten children in Rembang selected through purposive sampling. Data were collected through observation, interviews, questionnaires, product validation sheets, and fine motor skill tests. Data were analyzed using descriptive percentages, validity and reliability testing, independent sample t-test, and N-Gain. The media product took the form of a finger painting guide and activity set containing themes, tools, materials, safety procedures, and learning steps. Expert validation showed that the product was very feasible, with a media feasibility score of 92%. Teacher response reached 96%, and children's response reached 92%, both in the very positive category. The limited trial showed an N-Gain of 69.6%, categorized as moderately effective. The field trial also showed a significant improvement in children's fine motor skills. These findings indicate that finger painting is a valid, practical, and effective learning medium for stimulating hand-eye coordination, finger control, precision, creativity, and learning motivation in kindergarten children.